Investigation of knee control as a lower extremity injury risk factor: A prospective study in youth football - Räisänen, A. M.; Arkkila, H.; Vasankari, T.; Steffen, K.; Parkkari, J.; Kannus, P.; Forsman, H.; Pasanen, K. (Scandinavian Journal of Medicine & Science in Sports, 2018)
This prospective study in youth football examined the relationship between frontal plane knee projection angle (FPKPA) during the single-leg squat and sustaining an acute lower extremity injury or acute non-contact lower extremity injury. Secondly, side-to-side asymmetry in FPKPA and sex as injury risk factors were explored. In addition, we investigated the influence of age, sex and leg dominance on the FPKPA. A total of 558 youth football players (U11 to U14), participated in the single-leg squat test and prospective injury registration. FPKPA was not found as a risk factor for injuries at this age. There was no difference in the mean FPKPA between sexes. However, FPKPA was associated with age; oldest subjects displayed the smallest FPKPA. Among boys, the frontal plane knee control improved by age. Among girls, the relationship between age and FPKPA was not as clear but the oldest girls displayed the smallest mean FPKPA in the study (12.2°+ 8.3°). The FPKPA was greater on the dominant kicking leg compared to the non-dominant support leg (P<0.001 for boys, P=0.001 for girls). However, side-to-side asymmetry in FPKPA was not associated with future injuries. In conclusion, frontal plane knee control in the single-leg squat was not associated with lower extremity injuries among young football players. As the single-leg squat to 90° knee flexion was too demanding for many subjects, easier single-leg squat test procedure or a different movement control test, such as a double-legged squat, could be more suitable for the young football players.